Pengaruh Gaya Belajar VAK (Visual, Auditorial dan Kinestetik) Terhadap Kemampuan Berpikir Kritis Pada Mata Pelajaran Sejarah Indonesia Siswa Kelas XI IPA 2 SMA Negeri 7 Kota Serang - Shafa Syawalina; Agus Rustamana; Yuni Maryuni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
The aim of this research is to explain the influence of visual, auditory and kinesthetic learning styles on critical thinking skills in the Indonesian History subject of class XI IPA 2 students. This research uses quantitative methods with a pre-experimental design approach. A research design that observes one or more groups after being given a treatment or agent that is thought to cause change. The findings of this study indicate that each of the three learning style group Visual, Auditorial and Kinesthetic (VAK) significant effect on students overall critical thinking abilities. This is supported by the paired sample t test hypothesis test, resulting in a t_count value greater than the t_table value. In the visual group the resulting value was 14.209>2.160. Then the auditory group produced a score of 17.294>2.306 and the kinesthetic group with a score of 6.967>2.447. Students who are visual types when receiving information tend to use the visual sense modality. Furthermore, students with the auditory type use the auditory sense modality. And students with the kinesthetic type use the kinesthetic or physically oriented modality. Before being given treatment, the average pre-test score of students was classified as low or below the minimum completeness criteria. After receiving the learning, stundents average scores on the post-test exceeded the minimum passing standard. This increase can be seen in the comparison of pre-test and post-test scores which shows an increase in learning, this means that the treatment in the form of the learning process provided is classified as effective.